Evaluating the Effectiveness of Quality Improvement Strategies in Mid-Level Private Healthcare Facilities of Lagos State: A Donabedian Model-Based Approach - Nnenna, Mba-Oduwusi; Ifesinachi, Eze; Tochukwu, Osuji; Mubarak, Ahmed; Bolaji, Akala; Maxwell, Obubu; Tolulope, Oyekanmi; Oluwatosin, Kolade; Nkata, Chuku; Alozie, Ananaba; Rodio, Diallo; Firdausi, Umar Sadiq; et al. (Journal of Public Health International, 2024)
Background This study evaluates the effectiveness of quality improvement (QI) strategies in mid-level private healthcare facilities in Lagos State, with a focus on the structural components, healthcare processes, and healthcare outcomes. Employing the Donabedian model, the research aims to comprehensively assess and enhance healthcare service quality in these facilities. Methods A before-and-after study design was employed, involving a baseline assessment of 321 health facilities and endline assessment of 239 healthcare facilities, and a subsequent 10 - 12-month quality improvement intervention. Data were collected using facility assessments, client exit interviews, and interviews with key stakeholders. The analysis included a before and after analysis of the structural components, healthcare processes, and healthcare outcomes. Results The study demonstrates positive outcomes in mid-level private healthcare facilities in Lagos State following quality improvement (QI) interventions. Structural components, including, improved equipment availability, and enhanced compliance with standards, showcased significant improvements. Renovations and heightened registration compliance further underscored commitment to regulatory standards. Challenges in service availability, particularly in family planning and laboratory services, were identified. Importantly, the implementation of a QI scoring system revealed an overall positive impact, with the average score rising from 69% to 74%, signifying enhanced quality across diverse priority areas. Implications These findings highlight the success of QI interventions in transforming healthcare processes and structural components. Despite notable progress, persistent challenges in specific services call for targeted interventions. The substantial increase in patient satisfaction and overall QI scores underscores the transformative potential of sustained efforts and tailored interventions in mid-level private healthcare facilities in Lagos State. Conclusions This research comprehensively evaluates the effectiveness of quality improvement strategies implemented in mid-level private healthcare facilities in Lagos State, Nigeria, utilizing the Donabedian Model as a guiding framework. The findings provide valuable insights for policy recommendations, with the aim of aligning healthcare services with the Donabedian model to ensure the provision of high-quality care in mid-level private healthcare facilities in Lagos State. This study contributes to the ongoing efforts to improve healthcare quality in Lagos State. Contribution to Knowledge The research provides empirical insights into the effectiveness of quality improvement strategies in mid-level private healthcare facilities, particularly within the context of Lagos State, Nigeria. It highlights the significance of addressing structural components, optimizing healthcare processes, and monitoring healthcare outcomes to enhance the quality of care provided, aligning with the Donabedian model. These findings offer a valuable basis for policy recommendations and further research efforts aimed at improving healthcare quality in similar settings.
Keywords: healthcare quality; quality improvement; Donabedian model; healthcare facilities; patient satisfaction; contraceptive usage